Valuation techniques for conserving marine resources for ecotourism development - Latiff, Norasilah; Mohammad Afandi, Syamsul Herman; Zaiton, Samdin (Taylor's University, 2016)
The marine ecosystem is valuable for quality of life and economic growth. Basically, the function of the marine ecosystem can be classified into three groups: economic (resorts, chalet and hotels), social (recreational activities) and environmental. The development of resorts, recreational activities, offshore and aquaculture activities are just some examples. Due to poor unplanned management and overexploitation, marine ecosystems can face extensive damage. Therefore, the objective of this paper is to review the valuation techniques of conservation areas of marine resources for ecotourism development. In addition, this paper also aims to review the validity of methods that can be applied to determine the values of marine resources used in previous studies. Based on previous studies, economic valuation can be classified into non-market stated preference method and market based revealed preference method. In each group, several methods, are provided, for example, market price method, productivity method, hedonic pricing method, travel cost method, contingent valuation method, contingent choice method and benefit transfer method. Hence, the values can be used as a conversion of a quantity, quality or the changes of price (monetary value). The paper also highlights how the findings can be used as a future reference, especially in scope of valuing marine conservation area.